Giving Glycine Can Increase Melon Production Using a Hydroponic Spray System - Kusparwanti, Tri Rini; Anggraeni, Diah Kirana; Pertami, Rindha Rentina Darah; Suwardi, Suwardi; Ermawati, Netty; Meliah, Siti (P3M Politeknik Negeri Jember, 2024)
Cucumis melo L. is an annual plant and has high economic value so it is widely cultivated in Indonesia. Possible efforts include providing amino acids and hydroponic methods. Determining the provision of amino acids with the best concentration for the growth and quality of hydroponic plant production is the aim of this research. The research method was a completely randomized design (CRD) consisting of factors with four levels of amino acid concentration, namely G0 (without administration of amino acids), G1 (2 mgL-1), G2 (4 mgL-1) and G3 (6 mgL-1) Meanwhile the data was analyzed using the F test. The results for all parameters, both growth and production of melon plants, were not significantly different. Although the concentration of amino acids given to melon plants did not show any influence on the quality of hydroponic melon production, there was a good increase in diameter of 13.60 cm and fruit weight of 1.46 kg. Based on the administration of amino acids, it can be concluded that although it did not have a significant effect, the fruit diameter in the 6 mgL-1 treatment was the largest.